1982
DOI: 10.1063/1.330162
|View full text |Cite
|
Sign up to set email alerts
|

Deep radiative levels in InP

Abstract: Results of a detailed photoluminescence study of deep radiative transitions in InP crystals prepared by the bulk and epitaxial techniques are reported. In order to understand the origin of the photoluminescence (PL) spectra, bulk samples were subjected to isothermal anneals at different partial pressures of phosphorus. Similarly, the liquid phase epitaxy (LPE) wafers were grown with and without phosphorus in the gas stream. The electrical nature of some of the species responsible for the PL emission was inferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
23
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 25 publications
6
23
0
2
Order By: Relevance
“…PL spectra of all these samples exhibit additional bands C and D located at 1252 nm (0.99 eV) and 1652 nm (0.75 eV), respectively. Similar bands were observed [17] on LPE layers. Band C was also observed on melt grown and liquid encapsulated Czochralski bulks.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…PL spectra of all these samples exhibit additional bands C and D located at 1252 nm (0.99 eV) and 1652 nm (0.75 eV), respectively. Similar bands were observed [17] on LPE layers. Band C was also observed on melt grown and liquid encapsulated Czochralski bulks.…”
Section: Resultssupporting
confidence: 85%
“…Band C was also observed on melt grown and liquid encapsulated Czochralski bulks. Using high temperature annealing under different phosphorus pressure the band C was found to be connected to phosphorus vacancy (V P ) [17]. The origin of band D at 0.75 eV is still unknown.…”
Section: Resultsmentioning
confidence: 98%
“…The broad band at 1.21 eV is observed only on annealed SI samples and it is not observed on the as-grown and on the annealed n-type conducting InP. Similar level was observed on annealed melt grown InP samples [8]. Cd diffusion performed on those samples led to complete suppression of 1.21 eV band which supports the acceptor-like nature of the band.…”
supporting
confidence: 80%
“…Similar but somewhat different dependence was reported in Ref. [8], where a steady increase from 40 to 120 K has been observed with abrupt decrease above 120 K. The dependence of integrated intensity on inverse temperature indicates that phonon assisted transitions over a barrier are involved in the luminescence mechanism. The vacancy-impurity complexes and radiative deep level transitions in GaAs and InP have been discussed in terms of configuration coordinate models [9].…”
supporting
confidence: 71%
“…There have been only a few reports on band D [1,[3][4][5]. Most of these concluded that band D is due to complexes involving Vp and impurities (for example, Cu~,-Vv [4]).…”
mentioning
confidence: 99%